Perbedaan Jumlah Trombosit Pada Pasien TB Sebelum dan Setelah 1 Bulan Mengonsumsi Obat Anti TB - Taqarrasya, Asa; Wikandari, Ririh Jatmi; Rosidah, Umi (Poltekkes Kemenkes Semarang, 2025)
Tuberculosis (TB) is still one of the infectious diseases with the highest mortality rate in the world. WHO stated that Indonesia is the third country in the world with the most TB cases. Semarang is the third province in Indonesia with the highest TB cases. Although the mortality rate is high, in reality TB can be treated and prevented. Anti-TB drugs as TB treatment agents can cause side effects, one of which is a decrease in the number of platelets. The purpose of this study was to determine the difference in the number of platelets in TB patients before starting treatment and after one month of treatment with Anti-TB drugs. The study population was new tuberculosis patients. The study sample was taken according to the established criteria and obtained as many as 24 people, who were examined twice, namely before treatment and after 1 month of treatment. The results of this study stated that the average number of platelets before starting TB treatment was 340.875 cells/μL and after one month of treatment with Anti-TB drugs was 281.958 cells/μL. The Wilcoxon test showed a P value = 0.009. There was a significant difference in the number of platelets before starting TB treatment and after one month of treatment with Anti-TB drugs. TB treatment can affect blood conditions, including platelets. Thus, patients and their families are expected to better understand the importance of carrying out routine checks and not stopping treatment without medical consultation.